The Role of Emotional Intelligence in Enhancing Workplace Relationships and Performance - Hilmawan, Ipan (Management Studies and Business Journal (PRODUCTIVITY), 2024)
Emotional intelligence has been identified as a critical factor in helping employees adapt to rapid and unpredictable organizational change. The challenges employees face in this adaptation can have a negative impact on their performance and well-being. This research aims to examine the contribution of emotional intelligence in the employee adaptation process to organizational change. The research method used is a systematic literature review, by collecting articles from reputable international databases such as Scopus and Web of Science, using keywords related to emotional intelligence and organizational adaptation. The research results show that emotional intelligence plays a significant role in improving employee performance, psychological well-being and organizational commitment. The practical implications of this research highlight the importance of emotional intelligence training, the application of mindfulness practices, and a supportive leadership style to increase employee adaptation to change.